Penerapan Metode Field Trip Observation untuk Meningkatkan Wawasan Siswa di MTs Muhammadiyah 10 Gresik - Nabil, Wildan; Rossidy, Imron (ISLAMIKA, 2024)
The aim of this research is to examine the implementation of the field trip observation method in the learning process of students, focusing on their ability to adapt and modify themselves in their surroundings, and to identify the strengths and weaknesses of this method. This qualitative study employs ethnographic or field research methodology, with teachers and students under observation as the primary data sources. Secondary data sources include school profile information, field trip destination observation data, and observations of field trip learning strategies. Data collection techniques involve documentation, interviews, and observations. Data analysis proceeds incrementally, leading to conclusions. Findings indicate that using field trip observation methods enhances students' insights, exposes them to new experiences, and alleviates boredom associated with classroom learning. However, this method requires thorough planning and significant financial resources to implement effectively.